2018
DOI: 10.3390/molecules23092137
|View full text |Cite
|
Sign up to set email alerts
|

Complete Chloroplast Genomes from Sanguisorba: Identity and Variation Among Four Species

Abstract: The genus Sanguisorba, which contains about 30 species around the world and seven species in China, is the source of the medicinal plant Sanguisorba officinalis, which is commonly used as a hemostatic agent as well as to treat burns and scalds. Here we report the complete chloroplast (cp) genome sequences of four Sanguisorba species (S. officinalis, S. filiformis, S. stipulata, and S. tenuifolia var. alba). These four Sanguisorba cp genomes exhibit typical quadripartite and circular structures, and are 154,282… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 53 publications
2
40
0
Order By: Relevance
“…mVISTA revealed a low divergence between the genomes of the five Dicliptera species, suggesting that the cp genomes were conserved. The IR regions were more highly conserved than the SC regions and the coding regions were less variable than the non-coding regions, which is also found in other angiosperms (Gao Deng, 2018; Meng et al, 2018;Li, Zhao & Liu, 2018;Yan et al, 2019). Khakhlova & Bock (2006) suggested that gene divergence with less variability in the IR and coding regions may be a result of copy corrections during gene conversion, which can correct or delete the mutation.…”
Section: Sequence Variation Among Five Dicliptera Speciesmentioning
confidence: 57%
See 4 more Smart Citations
“…mVISTA revealed a low divergence between the genomes of the five Dicliptera species, suggesting that the cp genomes were conserved. The IR regions were more highly conserved than the SC regions and the coding regions were less variable than the non-coding regions, which is also found in other angiosperms (Gao Deng, 2018; Meng et al, 2018;Li, Zhao & Liu, 2018;Yan et al, 2019). Khakhlova & Bock (2006) suggested that gene divergence with less variability in the IR and coding regions may be a result of copy corrections during gene conversion, which can correct or delete the mutation.…”
Section: Sequence Variation Among Five Dicliptera Speciesmentioning
confidence: 57%
“…These structures are longer than the cp genome of A. paniculata (15,249 bp) (Ding et al, 2016). The genome size of all Dicilptera is relevant to LSC variation (Table 2) and this phenomenon has also been identified in other species (Zhao et al, 2018;Li, Zhao & Liu, 2018;Meng et al, 2018). mVISTA revealed a low divergence between the genomes of the five Dicliptera species, suggesting that the cp genomes were conserved.…”
Section: Sequence Variation Among Five Dicliptera Speciesmentioning
confidence: 80%
See 3 more Smart Citations